Knowledge engineering approach for power transformer asset management - Sachin S. Bhandari (2018)
The main objective of the utility company is to maximize the utilization of its existing assets during their life cycle meeting both engineering and financial requirements. However, the knowledge available in the utility is unstructured and often in tacit form. This paper presents a knowledge based system for the utility companies in order to make an optimal decision on power transformer with their utilization. CommonKADS methodology, a structured development for knowledge and expertise representation, is utilized for designing and developing knowledge based system. A case study of One MVA power transformer of Nepal Electricity Authority is presented. The results show that the reusable knowledge can be categorized, modelled and utilized within the utility company using the proposed methodologies. Moreover, the results depict that utility company can achieve both engineering and financial benefits from its utilization. © School of Engineering, Taylor's University.